Hubungan Pengetahuan Ibu Tentang Pemberian MPASI Dengan Kejadian Stunting - Wirastri, Dwi; Zulfiana, Yesvi (Journal of Fundus, 2025)
Background: Complementary Food for Breast Milk (MP-ASI) is a transitional food from breast milk to family food. There are various factors that influence the provision of MP-ASI, including maternal knowledge about the provision of MP-ASI. Purpose of the study: To determine the relationship between maternal knowledge about MP-ASI and the incidence of stunting in infants aged 6-12 months in the Narmada Health Center work area. Research method: The type of research used is quantitative research with a descriptive correlation design with a cross-sectional approach. The population in this study were mothers who had babies aged 6-12 months totaling 60 people. Data analysis used the chi-square test. Results of the study: There is a relationship between maternal knowledge and the incidence of stunting in infants aged 6-12 months with a p-value of 0.00 in the Narmada Health Center work area. Conclusion: The characteristics of respondents are mostly high school educated as many as 37 (61.7), the average job as a housewife (IRT) 35 (58.3%), while the knowledge of mothers is good as many as 28 (46.7%), the knowledge of mothers is sufficient as many as 18 (30.0%), knowledge is lacking as many as 14 (23.3%). While mothers who provide exclusive breastfeeding are 53 (88.3%).